Late Quaternary geology and geomorphology of the Elk Valley, southeastern British Columbia - George, H.; Gorman, W. A.; VanDine, D. F. (Canadian Journal of Earth Sciences, 1987)
Glacial stratigraphy and geomorphology of the bottom areas of the Elk Valley support the existence of one major ice advance, presumably during the late Wisconsinan. Its retreat probably occurred in two stages by orderly frontal withdrawal. Glacial Lake Elk, formed within the Elk Valley from meltwaters released by this glacier, was dammed initially by an ice plug from the Rocky Mountain Trench glacier at a point near Morrissey and subsequently less than 3 km upvalley from Elko. The lake drained in at least three stages.